Validation of the DigCompEdu Check-in Questionnaire through Structural Equations: A Study at a University in Peru - Lorena Martín Párraga; Carmen Llorente Cejudo; Julio Barroso Osuna (MDPI AG, 2022)
The technologization of society presents a great challenge for education in the twenty-first century; there is a need to face that challenge to be able to promote quality digital literacy. The use of the teacher's digital competence in terms of the safe and critical use of technologies is one of the key competencies that can guarantee educational success. The present study analyzes the reliability and validity of the DigCompEdu questionnaire for future teachers within the framework of digital competence improvement. This tool is centered on teacher orientation, with respect to their level of competence, through a self-evaluation of their strengths and needs for improvement in digital learning, according to its different dimensions: digital literacy, communication and collaboration with the organization; search and treatment of data, digital socialization; technological creativity and innovation. For its development, the exploratory and confirmatory factorial analysis (EFA and CFA) technique was utilized via structural equation modeling (SEM). A total of 1659 professors, who are employed at a university in Peru, completed the questionnaire. The analyses that were performed corroborated the reliability and validity of the instrument, as well as the different possibilities guaranteed by the validation method via structural equations. We underline the need to offer training for professors in the area of digital competence and endorse methodologies based on competencies that guarantee the use of valid and reliable tools.